The Incident of Sibling Rivalry on Child with Mother Breastfeeding During Pregnancy - Rahmawati, Shinta Alifiana; Dewi, Lukyta Pratika; Rohmah, Amrina Nur; Primindari, Risya Secha; Rahmawati, Elia Ika; Irawan, Dwi Dianita (Jurnal Midpro, 2022)
The interval of pregnancy needs to be considered for parents in planning pregnancy. Close proximity of births can trigger neglect of the first child physically and psychologically, which can cause jealousy due to the unpreparedness of sharing affection by their parents. If parents cannot share their attention properly, it will cause jealousy in their younger siblings which can lead to competition between siblings or commonly called sibling rivalry. This research is interesting and different from previous research because the informants are children with mothers who are pregnant or mothers who are breastfeeding. The purpose of the study was to determine the incidence of sibling rivalry in children with breastfeeding during pregnancy in the Gunem Public Health Center, Rembang Regency. This research uses a qualitative study using a phenomenological approach. This study uses a qualitative study with in-depth interviews and observations. The findings from this study showed that from six informants, 4 children experienced sibling rivalry and only 2 children did not experience sibling rivalry. The majority of mothers choose to stop breastfeeding their older children. Sibling rivalry by children like children wants to be tries to prevent the mother from breastfeeding her sister, tries to attract the mother's attention and does not allow the mother to carry her sister, even the child does not hesitate to pinch and hit his sister if the older sister feels neglected.